Effect of Zn:Al ratio and calcination time on structural properties of Zn-Al-O compound - Mekprasart, Wanichaya; Worasawat, Suchada; Tangcharoen, Thanit; Pecharapa, Wisanu (My University, 2016)
Zn-Al-O compounds were successfully synthesized via co-precipitation method at pH 8 followed by calcination process at 900 °C. Influence of different precursor (Zn:Al) ratio and calcination time on their structural properties and formation have been investigated. Varying Zn:Al ratio was conducted at 2:1, 1:1, 1:2 and 1:4 with different calcination time at 0, 2, 4, and 6 h. Phase transformation and morphologies were characterized by X-ray diffraction and field-emission scanning electron microscope. Moreover, chemical bonding of Zn-Al-O compound was analyzed by Raman spectroscopy. The results indicated that chemical bonding between Zn-Al oxide evidentially occurred in all samples in composite form and spinel structure. In addition, the amount of Al content considerably contributes to significant aggregation in zinc aluminate (ZnAl2O4) spinel crystalline phase affirmed by XRD result. Meanwhile, SEM images reveal high crystallinity and strong formation of the compound obtained by prolong calcined period.
Keywords: Calcination time; Structural properties; Zn-Al-O compound; Zn:Al ratio